Maximizing human development. (17th May 2013) - Engineer, Merwan; King, Ian
Abstract: The Human Development Index (HDI) is widely used as a measure of well‐being. We examine the allocations implied by the maximization of this index using a standard growth model. Maximization leads to consumption (excluding education and health expenditures) being pushed to minimal levels. It also leads to the overaccumulation of education and/or health capital and possibly physical capital, relative to the standard golden rule. We propose an alternative specification for the HDI, where consumption replaces income as a proxy for decent standard of living. Maximization of this alternative implies a 'human development golden rule' which balances consumption, education and health expenditure. We advocate the method of optimization subject to constraints for revealing the policy implications of taking an achievement measure and its underlying philosophy seriously. Abstract : Maximiser le développement humain . L'indice de développement humain (IDH) est vastement utilisé comme mesure de bien‐être. A l'aide d'un modèle croissance conventionnel, on examine les implications pour l'allocations des ressources quand on veut maximiser cet indice. La volonté de maximisation mène à réduire au minimum la consommation (à l'exclusion des dépenses d'éducation et de santé). Voilà qui entraîne une sur‐accumulation du capital éducation et/ou santé, et peut‐être du capital physique, par rapport à ce que suggère la règle d'or conventionnelle. On propose une spécification de rechange de l'indice IDH ou la consommation remplace le revenu comme métrique pour mesurer un niveau de vie décent. La maximisation de cette métrique de rechange mène à une « règle d'or du développement humain » qui balance les dépenses de consommation, d'éducation et de santé. On défend cette méthode d'optimisation sous contraintes pour révéler les implications politiques qu'il y a à prendre au sérieux une mesure de résultat et la philosophie qui la sous‐tend.